Single‐Walled Metal–Organic Nanotube Built from a Simple Synthon. Issue 11 (19th January 2015) - Adarsh, Nayarassery N.; Dîrtu, Marinela M.; Naik, Anil D.; Léonard, Alexandre F.; Campagnol, Nicolo; Robeyns, Koen; Snauwaert, Johan; Fransaer, Jan; Su, Bao Lian; Garcia, Yann
Abstract A conformationally flexible triazole‐carboxylic acid ligand derived from an L‐amino acid, namely, 4 H‐1, 2, 4‐triazol‐4‐yl‐acetic acid (αHGlytrz), has been exploited to synthesize a structurally diverse and functionally intriguing metal–organic framework with CuSiF6. The crystal structure reveals a novel single‐walled metal–organic nanotube (SWMONT), namely, {[Cu3(μ3‐OH)(H2O)3(Glytrz)3]⋅SiF6⋅8 H2O⋅X}∞ (1), (where X=disordered lattice water molecules) having a pore size as large as zeolites. Compound 1 was synthesized as crystals, as powder, or as layers by precipitation/electrodeposition. Mercury intrusion porosimetry demonstrates the ability of this material to store metallic mercury, after a pressure treatment, contrary to previous literature examples.